Genomic medicine and developing countries: creating a room of their own - Séguin, Béatrice (Nat Rev Genet, 2008)
The notion that developing countries must wait for the developed world to make advances in science and technology that they later import at great cost is being challenged. We have previously argued that developing countries can harness human genetic variation to benefit their populations and economies. Based on our empirical studies of large-scale population genotyping projects in Mexico, India and Thailand, we describe how these resources are being adopted to improve public health and create knowledge-based economies. A significant additional benefit is building the capacity for scientific research and internalizing advances in technology, whatever their source.